2008
DOI: 10.1503/cmaj.061743
|View full text |Cite
|
Sign up to set email alerts
|

Systematic evaluation of errors occurring during the preparation of intravenous medication

Abstract: Interpretation: Our data suggest that the reduction of provider fatigue and production of pediatric-strength solutions or industry-prepared infusions may reduce medication errors. AbstractFrom the Department of Critical

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
83
1
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(93 citation statements)
references
References 35 publications
6
83
1
3
Order By: Relevance
“…Adapa et al 11 reported that preparing infusions at the bedside in this emergent simulation resulted in an odds ratio of 17.0 (95% CI, 5.2-55) for making a medication error compared with preparing the infusions in a calmer environment or having the infusions prepared in the pharmacy. Other evidence [12][13][14][15] has highlighted the error-prone nature of preparing critical infusions at the bedside, including vasopressors and opioids. Task analysis 16 has identified a total of 41 potential steps in the process of preparing a drug infusion, providing 41 opportunities for error during the fast-paced environment of medical emergencies.…”
Section: Simulationmentioning
confidence: 99%
“…Adapa et al 11 reported that preparing infusions at the bedside in this emergent simulation resulted in an odds ratio of 17.0 (95% CI, 5.2-55) for making a medication error compared with preparing the infusions in a calmer environment or having the infusions prepared in the pharmacy. Other evidence [12][13][14][15] has highlighted the error-prone nature of preparing critical infusions at the bedside, including vasopressors and opioids. Task analysis 16 has identified a total of 41 potential steps in the process of preparing a drug infusion, providing 41 opportunities for error during the fast-paced environment of medical emergencies.…”
Section: Simulationmentioning
confidence: 99%
“…• Medication reconciliation † (resulted in 1 medication order being changed for every 2.5 patients admitted) 21 • Satellite pharmacy 72,73 • Support for dose adjustments for patients with renal or liver failure*…”
Section: Pharmacistsmentioning
confidence: 99%
“…A Canadian study involving the preparation of infusions found that 34.7% of prepared infusions had concentration errors. 40 Another study evaluating i.v. preparation and administration errors demonstrated a rate of 13-84% in the United Kingdom, Germany, and France.…”
Section: IV Medicationsmentioning
confidence: 99%